Electro-viscoelastic response of an acrylic elastomer analysed by digital image correlation. (11th July 2017) - Thylander, S; Menzel, A; Ristinmaa, M; Hall, S; Engqvist, J
Abstract: Experimental investigations are presented with respect to the electromechanically coupled and time-dependent behaviour of an acrylic elastomer, VHB 4910. For the electromechanically coupled experiments different biaxial pre-stretches have been considered and full-field measurements were made using three-dimensional surface digital image correlation. Both equi-biaxial and non equi-biaxial pre-stretches as well as both circular and non-circular electrodes are investigated. The experimental data provide new insights into the complex material behaviour of VHB 4910 and will enable enhanced calibration and development of constitutive models. Special emphasis lies on the quantification of out-of-plane deformation, i.e. the thickness change, of biaxially pre-stretched specimens based on an assumption of material incompressibility. The level of pre-stretch and thickness of the membrane plays a critical role in view of electromechanical instabilities. For completeness, cyclic uniaxial tests of the purely mechanical response are also presented and compared to similar experiments found in the literature.